Assessment of the effectiveness of public participation in environmental impact assessment: a case study of Matseke filling station development - Rikhotso, Shenen (My University, 2023)
The process of Environmental Impact Assessment (EIA) aims at identifying the significant environmental, social, and economic impacts of a proposed project before a decision is made of whether a project should commence. The Public Participation Process (PPP) should occur throughout all phases of an EIA process and forms an integral part of successful EIAs. It allows for input from stakeholders and subsequently contributes to sustainable development. This process is however often viewed as a “box-ticking” exercise negatively impacting the intended effectiveness thereof. This study therefore aimed to assess the perceived effectiveness of public participation in EIA processes of the Matseke filling station project in the Capricorn District of Limpopo from the perspective of various key stakeholders. The study was descriptive and exploratory in nature and a qualitative research approach was considered pragmatic. Two key informant interviews were undertaken with the environmental assessment practitioner (EAP) and government official that was involved in the EIA processes. Furthermore, a total of 16 Interested and Affected Parties (I&APs) were identified to participate in the study. Different methods of qualitative analyses were used to analyse the objectives of this study. The methods include thematic analysis and descriptive statistics such as percentages and frequencies. The Statistical Package for Social Science (SPSS) version 24.0 software was used to analyse the data. The study findings show that the identified I&APs indicated that they were not involved in project planning and design. It further shows that only one I&AP commented during the process. Education, language, gender and methods of communication were identified as key factors in determining level and effectiveness of public participation processes. The study recommends that potential I&APs need to be educated by EAPs and government officials as to the role they play in ensuring effective public participation
Thesis (M.Sc. (Geography)) -- University of Limpopo, 2023
Keywords: Public Participation; Environmental Management Assessment; Environmental impact analysis; Ecological risk assessment; Public administration -- Citizen participation